Analysis of Figurative Language in Short Story “The Bet” a Work by Anton Chekhov 1889 - Syam, Dewi Fatikah; Dahniar, Dahniar (English Literature Studi Program Universitas Islam Makassar, 2024)
This research aims to figure out the types of figurative language used in the short story “The Bet” by Anton Chekhov and also to figure out the meaning of the figurative language used in the short story “The Bet” by Anton Chekov. The research method used is descriptive-qualitative. To obtain data, the research was conducted by reading the entire short story “The Bet,